Sensing without Seizing: The Institutional Barriers to AI Adoption in Indonesian MSMEs - Dadet Sugiarto; Eryco Muhdaliha; Jemmy Jemmy; Selamet Riyadi (PT. Anagata Sembagi Education, 2025)
Despite strong policy support, the adoption of Artificial Intelligence (AI) among Indonesian Micro, Small, and Medium Enterprises (MSMEs) remains critically low, creating a notable